THE DESCRIPTION OF MULTIMEDIA VOCITAS AS AN INTEGRATIVE UNIT FOR IMPROVING THE SOCIAL PEDAGOGICAL ACTIVITY OF STUDENTS - Rahimova Feruza Najmiddinovna; Rasulova Asilakhon Davronjon qizi (Journals Park Publishing, 2023)
In this article, the improvement of the socio-pedagogical activity of students in Multimedia Voices is described as an integrative unit in the process of socialization of students and factors.
Keywords: tool, socialization, integrative, activity, improvement, student, factor, cube.